2009
DOI: 10.1182/blood-2008-07-165167
|View full text |Cite
|
Sign up to set email alerts
|

Leaky severe combined immunodeficiency and aberrant DNA rearrangements due to a hypomorphic RAG1 mutation

Abstract: The RAG1/2 endonuclease initiates programmed DNA rearrangements in progenitor lymphocytes by generating doublestrand breaks at specific recombination signal sequences. This process, known as V(D)J recombination, assembles the vastly diverse antigen receptor genes from numerous V, D, and J coding segments. In vitro biochemical and cellular transfection studies suggest that RAG1/2 may also play postcleavage roles by forming complexes with the recombining ends to facilitate DNA end processing and ligation. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 70 publications
(107 reference statements)
1
62
0
Order By: Relevance
“…In detail, after initial purification of DN4 stage T cells by flow sorting, single cells were resorted or isolated by using the CellCelector automated cell picking system (ALS Automated Lab Solutions GmbH, Jena, Germany); digested in a 20-l solution containing 10 mM Tris-HCl (pH 9.0), 50 mM KCl, 1.5 mM MgCl 2 , 3.0 g proteinase K (EM Science), and 0.1% Triton X-100 (Sigma); and incubated at 55°C for 60 min followed by 95°C for 15 min. First-round PCR amplified both V(D)Jrearranged alleles together in a 60-l final reaction mixture volume consisting of 20 l of the single-cell isolation solution described above, PCR buffer (10 mM Tris-HCl [pH 9.0], 50 mM KCl, and 2.0 mM MgCl 2 ), 200 M deoxynucleoside triphosphates (dNTPs), 0.5 U Taq DNA polymerase (New England BioLabs), and an oligonucleotide mixture (each at a 100 nM final concentration) (25,26,42,82) (Table 4) containing 22 forward primers corresponding to 23 V␤ exon families (2 primers were designed to amplify 2 V␤5 and 3 V␤8 multisequence families, respectively), the D␤1 and D␤2 diversity segment genes, 2 reverse primers matching joining-segment J␤1 and J␤2 sequences, as well as 1 primer set for ␤-actin. The PCR conditions were 94°C for 1 min and 5 cycles with the annealing temperature ramped from 66°C to 58°C, followed by 25 cycles of 94°C for 30 s, 56°C for 60 s, and 72°C for 60 s, with a final extension step at 72°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…In detail, after initial purification of DN4 stage T cells by flow sorting, single cells were resorted or isolated by using the CellCelector automated cell picking system (ALS Automated Lab Solutions GmbH, Jena, Germany); digested in a 20-l solution containing 10 mM Tris-HCl (pH 9.0), 50 mM KCl, 1.5 mM MgCl 2 , 3.0 g proteinase K (EM Science), and 0.1% Triton X-100 (Sigma); and incubated at 55°C for 60 min followed by 95°C for 15 min. First-round PCR amplified both V(D)Jrearranged alleles together in a 60-l final reaction mixture volume consisting of 20 l of the single-cell isolation solution described above, PCR buffer (10 mM Tris-HCl [pH 9.0], 50 mM KCl, and 2.0 mM MgCl 2 ), 200 M deoxynucleoside triphosphates (dNTPs), 0.5 U Taq DNA polymerase (New England BioLabs), and an oligonucleotide mixture (each at a 100 nM final concentration) (25,26,42,82) (Table 4) containing 22 forward primers corresponding to 23 V␤ exon families (2 primers were designed to amplify 2 V␤5 and 3 V␤8 multisequence families, respectively), the D␤1 and D␤2 diversity segment genes, 2 reverse primers matching joining-segment J␤1 and J␤2 sequences, as well as 1 primer set for ␤-actin. The PCR conditions were 94°C for 1 min and 5 cycles with the annealing temperature ramped from 66°C to 58°C, followed by 25 cycles of 94°C for 30 s, 56°C for 60 s, and 72°C for 60 s, with a final extension step at 72°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Second, germline NHEJ/Tp53-deficient mice succumb to pro-B lymphomas with RAG-dependent Igh/c-myc or Igh/N-myc translocations (Difilippantonio et al, 2002;Zhu et al, 2002;Gladdy et al, 2003;Rooney et al, 2004). Third, Tp53 À/À mice expressing a RAG1 mutant that exhibits defects in DNA end joining develop thymic lymphomas with clonal antigen receptor locus translocations (Giblin et al, 2009). Fourth, Tp53 À/À mice containing a genetic block in thymocyte development succumb to thymic lymphomas with RAG-dependent genomic instability (Haines et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Mouse models of OS and of leaky SCID have been generated, such as Rag1 R972Q, 16 the Rag1 S723C, 7 , and Rag2 R229Q 17 mice. In addition to the mouse, SCID and SCID variants have also been modeled in the dog and horse.…”
Section: Cd8mentioning
confidence: 99%
“…We and others have shown that hypomorphic RAG mutations that affect, but do not abolish, V(D)J recombination, are often associated with distinct immunologic and clinical phenotypes with residual presence of T, and in some cases B, lymphocytes. [6][7][8][9] The presence of autologous, auto-reactive, activated, and oligoclonal T cells that infiltrate and damage peripheral organs is a hallmark of Omenn syndrome (OS). In other cases, hypomorphic RAG mutations may cause delayed disease onset, granuloma formation, autoimmunity, and/or dysgammaglobulinemia.…”
Section: Introductionmentioning
confidence: 99%